Early responses to 3 mm resilient stabilization appliance therapy for sub-acute and chronic temporomandibular disorder pain predict 12-months follow-up outcomes. Issue 1 (2nd January 2022) - Emshoff, R diger; Bertram, Annika; Stigler, Robert Gerhard; Schnabl, Dagmar
ABSTRACT: Objective : To estimate whether outcomes at 12-month follow-up may be predicted by an intermediate and early response to a 3 mm resilient splint therapy for unilateral arthralgia and myofascial pain assessed at 3- and 6-month follow-ups. Methods : Data obtained from one retrospective cohort study consisting of 78 patients suffering from chronic and sub-acute unilateral arthralgia and myofascial pain who were managed with 3 mm resilient splint therapy were subjected to analysis. Results : Baseline visual analog scale (VAS) intensity, gender as well as changes in the intensity of VAS pain at 3- and 6-month follow-ups predicted unilateral arthralgia and myofascial pain group membership ( p < .001). The function classified 83.3% of the cross-validated and 87.2% of original grouped cases correctly. Discussion : The proposed model may be used to timely identify patients who are at risk of developing prolonged non-responsive unilateral arthralgia and myofascial pain chronicity.